Application-based company mergers in the digital era: Unpacking the legal challenges - Anna Maria Tri Anggraini; Sharda Abrianti; Gisca Nurannisa; Jimi Rambo Arranchado; Yosefa Oktriviani Mutiara Mali (Universitas Ahmad Dahlan, 2026)
Introduction to the Problem: The rapid expansion of digital markets, driven by network effects and data concentration, challenges traditional merger control frameworks, particularly due to the risk of market “tipping” toward dominant platforms in jurisdictions such as Indonesia, the United States, China, and the European Union. Purpose/Study Objectives: To examine the criteria used by competition authorities in assessing mergers involving application-based companies and their implications for fair competition in digital markets. Design/Methodology/Approach: This study employs a normative juridical method with a comparative approach, analysing merger control regimes in Indonesia, the European Union, the United States, and China, including key assessment tests such as SLC, SIEC, and dominance-based approaches. Findings: The study finds that traditional indicators such as market share and transaction value are insufficient to capture competitive risks in digital markets. Mergers may reinforce data control, ecosystem dominance, and eliminate potential competition without immediate effects on market structure. Therefore, competition authorities should adopt more forward-looking assessments that consider data, innovation, and tipping risks, alongside stronger pre- and post-merger oversight to protect long-term competition and consumer welfare. Paper Type: Research Article